EXAMINATION OF COVID-19 FEAR IN TERMS OF ITS DEFINING CHARACTERISTICS - Sevim ÇİMKE; Dilek YILDIRIM GÜRKAN; Derya ESENKAYA (Rojan GÜMÜŞ, 2021)
The study aims to determine the fear of coronavirus and its affecting factors. It was conducted as a cross-sectional study. Data on participants were collected using an online questionnaire spread throughout social media, e-mail, and WhatsApp groups. Socio-demographic questionnaire form, COVID-19 Fear Scale, and Visual Analogue Scale (VAS) were used to collect data. Number, percentage, mean, t-test, One-Way ANOVA, and Pearson correlation analysis were used to evaluate the research data. The research was completed with 727 people. A statistically significant relation was found between the COVID-19 fear with age, gender, marital status, having children, having a chronic disease, working status and being health personnel, watching coronavirus news, and always talking about coronavirus at-home settings. Accordingly, it is recommended to determine the fear of coronavirus in society, to identify high-risk individuals by performing community screenings, and to provide psychological support. It is very important to diversify and implement protective intervention programs to reduce some of the psychological consequences of fear and fear.